Sex differences in postural stability indices among competitive swimmers and untrained individuals - Tomasz Chomiuk; Przemysław Kasiak; Kaja Romanowska; Artur Mamcarz; Daniel Śliż (Medical Research Journal)
INTRODUCTION: To compare differences in overall stability index (OSI), anterior/posterior stability index (APSI), and medial/lateral stability index (MLSI) between males and females among swimmers and untrained individuals. MATERIALS AND METHODS: The study recruited 30 (Nmales = 15, age = 21.8 ± 1.4 years old, weight = 70.9 ± 8.7 kg, height = 175.5 ± 7.8 cm) swimmers and 30 (Nmales = 15, age = 20.1 ± 1.4 years old, weight = 71.3 ± 13.5 kg, height = 174.8 ± 11.0 cm) healthy controls. Participants underwent body stability tests on the BIODEX Balance Platform in a two-footed stance, on the right leg, and the left leg. Participants underwent the tests in three 30-sec averaged trials. Compared were OSI, APSI, and MLSI between male and female athletes and controls. RESULTS: OSI, APSI, and MLSI did not differ between sexes among swimmers (p = 0.09–0.92). Females have lower stability indices than males among controls. OSI [1.50 (0.65) vs. 2.00 (1.80); p = 0.004], APSI [0.90 (0.60) vs. 1.30 (1.10); p = 0.02] and MLSI [0.70 (0.40) vs. 1.00 (1.15); p = 0.004] were different between sexes in the controls during two-footed stance. OSI [2.20 (1.15) vs. 3.10 (1.18); p = 0.04] and MLSI [1.10 (0.80) vs. 2.10 (0.90); p = 0.03], but no APSI [1.60 (0.90) vs. 1.70 (1.05); p = 0.10) also differed between male and female controls on right leg standing. Finally, OSI [2.10 (1.30) vs. 3.20 (1.85); p = 0.04) and APSI [1.30 (0.87) vs. 2.20 (1.30); p = 0.01] on left leg standing were significantly lower among females than males controls. MLSI [1.20 (0.85) vs. 1.80 (1.05); p = 0.10] on the left leg did not differ significantly. CONCLUSIONS: Untrained females have a significantly lower majority of stability indices than untrained males. Swimmers did not have sex differences between any of the stability indices. Swimming training may mitigate sex differences in postural stability, suggesting its potential role in balance training programs.